Combinatorial Therapeutic Approaches with Nanomaterial-Based Photodynamic Cancer Therapy - Yang Hao; Chih Kit Chung; Zhenfeng Yu; Ruben V. Huis in ‘t Veld; Ferry A. Ossendorp; Peter ten Dijke; Luis J. Cruz (Pharmaceutics, 2022)
Photodynamic therapy (PDT), in which a light source is used in combination with a photosensitizer to induce local cell death, has shown great promise in therapeutically targeting primary tumors with negligible toxicity and minimal invasiveness. However, numerous studies have shown that noninvasive PDT alone is not sufficient to completely ablate tumors in deep tissues, due to its inherent shortcomings. Therefore, depending on the characteristics and type of tumor, PDT can be combined with surgery, radiotherapy, immunomodulators, chemotherapy, and/or targeted therapy, preferably in a patient-tailored manner. Nanoparticles are attractive delivery vehicles that can overcome the shortcomings of traditional photosensitizers, as well as enable the codelivery of multiple therapeutic drugs in a spatiotemporally controlled manner. Nanotechnology-based combination strategies have provided inspiration to improve the anticancer effects of PDT. Here, we briefly introduce the mechanism of PDT and summarize the photosensitizers that have been tested preclinically for various cancer types and clinically approved for cancer treatment. Moreover, we discuss the current challenges facing the combination of PDT and multiple cancer treatment options, and we highlight the opportunities of nanoparticle-based PDT in cancer therapies.